Assessment of air quality benefits from the national pollution control policy of thermal power plants in China: A numerical simulation. (April 2015) - Wang, Zhanshan; Pan, Libo; Li, Yunting; Zhang, Dawei; Ma, Jin; Sun, Feng; Xu, Wenshuai; Wang, Xingrun
Abstract: In 2010, an emission inventory of air pollutants in China was created using the Chinese Bulletin of the Environment, the INTEX-B program, the First National Pollution Source Census, the National Generator Set Manual, and domestic and international research studies. Two emission scenarios, the standard failed emission scenario (S1) and the standard successful emission scenario (S2), were constructed based upon the Instructions for the Preparation of Emission Standards for Air Pollutants from Thermal Power Plants (second draft). The Fifth-Generation NCAR/Penn State Mesoscale Model (MM5) and the U.S. EPA Models-3 Community Multiscale Air Quality (CMAQ) model were applied to China to study the air quality benefits from Emission Standards for Air Pollutants from Thermal Power Plants GB13223-2011 . The performance of MM5 and CMAQ was evaluated with meteorological data from Global Surface Data from the National Climatic Data Center (NCDC) and the daily Air Pollution Index (API) reported by Chinese local governments. The results showed that the implementation of the new standards could reduce the concentration of air pollutants and acid deposition in China by varying degrees. The new standards could reduce NO2 pollution in China. By 2020, for the scenario S2, the area with an NO2 concentration higher than the second-level emission standard, and the average NO2 concentration in 31 selected provinces would be reduced by 55.2% and 24.3%, respectively. The new standards could further reduce the concentration of declining SO2 in China. By 2020, for S2, the area with an SO2 concentration higher than the second-level emission standard and the average SO2 concentration in the 31 selected provinces would be reduced by 40.0% and 31.6%, respectively. The new standards could also reduce PM2.5 pollution in China. By 2020, for S2, the area with a PM2.5 concentration higher than the second-level emission standard and the average concentration of PM2.5 in the 31 selected provinces would be reduced by 17.2% and 14.7%, respectively. The new standard could reduce nitrogen deposition pollution in China. By 2020, for S2, the area with a nitrogen deposition concentration >2.0 tons·km −2 and the total nitrogen deposition in China would be reduced by 28.6% and 16.8%, respectively. The new standards could reduce sulfur deposition pollution in China. By 2020, for S2, the area with a sulfur deposition >1.5 tons·km −2 and the total sulfur deposition in China would be reduced by 55.3% and 21.0%, respectively. Highlights: We create an emission inventory of air pollutants in China based on the standard. The new emission standard will significantly improve air quality in China in 2020. Improvement of SO2, NO2, PM2.5 and acid deposition are simulated. Air quality improvement is evaluated in national, regional and urban scale. We offer additional suggestions to further improve air quality in key regions.